1964
DOI: 10.2472/jsms.13.190
|View full text |Cite
|
Sign up to set email alerts
|

On the Elevated-Temperature Strengths of Some Aluminium Cast Alloys for Piston

Abstract: Table I and II, respectively.The specimens were cast into a permanent mould which is in accordance with Japanese Industrial Standard (JIS) H0321.The alloys were compared on the basis of their tensile properties at elevated-temperature after 1000 hour soaking. The creep tests were carried out with the lever-type creep-rupture tester, and the creep strengths were calibrated at 0.1% per 1000 hours.The fatigue tests were conducted on Ono's high-temperature fatigue tester (3000rpm) and fatigue strengths were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They exhibit not only a relatively high elevated temperature strength but resist as well thermal fatigue, which indicates a composite‐like behaviour with load transfer from the Al‐matrix to stiffer intermetallic phases. It has been reported that Ni improves the high temperature strength of AlSi alloys36 due to the presence of Ni aluminides such as Al 3 Ni and Al 9 FeNi 37–39. The effect of 1 wt% Ni addition on the architecture, strength and thermal cycling creep resistance of an AlSi12 alloy was investigated in ref 40, 41…”
Section: Strength Of Alsi Alloys Reinforced With Fe and Ni Aluminmentioning
confidence: 99%
“…They exhibit not only a relatively high elevated temperature strength but resist as well thermal fatigue, which indicates a composite‐like behaviour with load transfer from the Al‐matrix to stiffer intermetallic phases. It has been reported that Ni improves the high temperature strength of AlSi alloys36 due to the presence of Ni aluminides such as Al 3 Ni and Al 9 FeNi 37–39. The effect of 1 wt% Ni addition on the architecture, strength and thermal cycling creep resistance of an AlSi12 alloy was investigated in ref 40, 41…”
Section: Strength Of Alsi Alloys Reinforced With Fe and Ni Aluminmentioning
confidence: 99%
“…This spheroidization of the eutectic Si limits the use of AlSi12 cast alloys for high-temperature applications. The addition of transition elements such as Ni and Cu are considered to be an effective way to improve the high-temperature strength of cast Al–Si alloys in as-cast and solution-treated conditions by forming stable aluminides [10–15] . Recently, we have shown that the higher high-temperature strength exhibited by AlSi12Ni as compared to a Ni-free AlSi12 alloy is conferred by a highly interconnected 3-D structure formed by 20 vol.% of eutectic Si, Al 9 FeNi and Al 15 Si 2 (FeMn) 3 aluminides [9] .…”
Section: Introductionmentioning
confidence: 99%